Low replicability can support robust and efficient science - Stephan Lewandowsky (Nature Portfolio, 2020)
There has been much concern about the “replication crisis” in psychology and other disciplines. Here the authors show that an efficient solution to the crisis would not insist on replication before publication, and would instead encourage publication before replication, with the findings marked as preliminary.